Soil microbial properties influenced with long term application of manures and fertilizers - SHEORAN, SUNITA; RAJ, DEV; ANTIL, R S; MOR, V S; GREWAL, K S (The Indian Journal of Agricultural Sciences, 2020)
An ongoing long-term field experiment established in 1995 at CCS Haryana Agricultural University, Hisar (India) under pearl millet-wheat cropping system was selected to examine the impact of organic manures and fertilizers on soil microbiological properties. After 19 years of experiment, the samples were collected after wheat harvest in April, 2014. Under different combinations of treatments, the microbial biomass carbon (MBC) and microbial biomass nitrogen (MBN) content in soil ranged from 202–491 and 35.0–79.8 mg/kg, respectively. The lower content of MBC and MBN was observed in farmyard manure (FYM) treated plots as compared to pressmud or poultry manure. Soil microbial quotient (SMQ) ranged from 3.18– 5.61% and higher SMQ was observed with pressmud and poultry manure application as compared to FYM application. The highest dehydrogenase activity (DHA) was reported with FYM15 (63.71 μgTPF/g/24 hr) which was statistically at par with FYM15N150 (59.75 μg TPF/g/24 h) and pressmud7.5 (58.14 μg TPF/g/24 h). Among organic manures applied alone alkaline phosphatase activity (APA) followed the order: poultry manure>FYM>pressmud. The highest urease activity (97.6 μg NH4 +-N/g/h) was observed with pressmud7.5 and this may be attributed to higher N content (3.23%) in pressmud. The dehydrogenase and urease activity decreased in the plots where organic manures were applied in conjunction with NP fertilizers as compared to solitary application of organic manures. However, reverse trend was observed in case of alkaline phosphatase. Overall, pressmud applications exhibited favorable impacts on soil properties under pearl millet wheat cropping. Therefore, continuous application of pressmud could lead to long term maintenance of soil microbial properties in these sandy loam soils.